A Rechargeable Zn–Air Battery with High Energy Efficiency and Long Life Enabled by a Highly Water‐Retentive Gel Electrolyte with Reaction Modifier. Issue 22 (17th April 2020) - Song, Zhishuang; Ding, Jia; Liu, Bin; Liu, Xiaorui; Han, Xiaopeng; Deng, Yida; Hu, Wenbin; Zhong, Cheng
Abstract: Tremendous effort have recently been made in optimizing the air catalysts of flexible zinc–air batteries (ZABs). Unfortunately, the bottleneck factors in electrolytes that largely limit the working life and energy efficiency of ZABs have long been relatively neglected. Herein, an alkaline gel polymer electrolyte (GPE) is fabricated through multiple crosslinking reactions among poly(vinyl alcohol) (PVA), poly(acrylic acid), and graphene oxide followed by intense uptake of an alkali and the KI reaction modifier. The prepared GPE exhibits essentially improved properties compared to traditional PVA gel electrolyte in terms of mechanical strength, ionic conductivity, and water retention capability. In addition, the introduced reaction modifier I − in the GPE changes the path of the conventional oxygen evolution reaction, leading to a more thermodynamically favorable path. The optimized GPE enables flexible ZABs exhibiting an exceptionally low charge potential of 1.69 V, a long cycling time of 200 h, a high energy efficiency of 73%, and rugged reliability under different extreme working conditions. Moreover, the successful integration of ZABs in a variety of real wearable electronic devices demonstrates their excellent practicability as flexible power sources. Abstract : Electrolytes play a significant role in the development of high‐energy‐density and long‐life rechargeable zinc–air batteries. A developed KI–PVAA–GO hydrogel electrolyte enables zinc–air batteries that exhibit low charge potential of 1.69 V, long working life of 200 h, high energy efficiency of 73%, and excellent practicability for flexible power sources.